(untitled) (Fractal: Journal of Psychology, 2009)
This is a theoretical study about a particular theme. This article intends to relate about the excessive consumption in the contemporaneity and a possible relation with the addiction. We do a psychoanalytical and interdisciplinary approach. Social and cultural aspects of the consumer way of life are introduced and how they influence the psychopathology of the current time, described for some authors as “post-modernity”. We intend to analyze, from a psychoanalytical conception of addiction, the constructed relation between the subject and the excessive consumption object and respective representations. The actual psychopathology is described as marked for the culture of excessive narcissism.